Influence Green Corporate Strategy and Cross Sector CollaborationTowards Improving the Performance of MSMEs in Lagoa Subdistrict - Pristanto Ria Irawan; Taryanto Taryanto; Wa Ode Yusti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The purpose of this study is to investigate how green corporate strategy and cross sector collaboration might enhance the performance of MSMEs in Lagoa Utara Village, North Jakarta. MSMEs must develop strong synergies with a variety of actors in their business strategies, such as the government, private sector, academia, and communities, in order to meet the difficulties of economic upheaval and urban market dynamics. 90 MSMEs from a variety of business sectors participated in a survey as part of the quantitative research approach. Data was gathered using structured questionnaires, and multiple linear regression models were employed for analysis. The study's findings show that while cross-sector collaboration has a significant impact on MSME performance, green corporate strategy has a partial lack of significant influence. Additionally, both cross-sector collaboration and green corporate strategy have a positive and significant impact on improving MSME performance in North Jakarta's Lagoa subdistrict. The findings of this study have significant ramifications for the creation of cooperation-based policies that encourage the expansion of MSMEs in metropolitan regions like North Jakarta's Lagoa Utara subdistrict.